Preparation, physico-chemical and spectroscopic investigation of thiacetazone and quinalizarin complexes with Mn(II), Fe(II), Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Pb(II) - Shaker S.A.; Mohammed H.A.; Salih A.A. (2023)
Some new complexes of thiacetazone (Thz) and quinalizarin (Qz) with Mn(II), Fe(II), Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Pb(II) were prepared. The ligands and their metal complexes were characterized by phisco-chemical spectroscopic techniques. The spectral data suggested that the thiacetazone as a neutral bidentate ligand is coordinated with the metal ions through the N and S atoms. The quinalizarin is negatively charged as a bidentate ligand and it is coordinated with the metal ions through the two O atoms. It is concluded that all the complexes of divalent metal ions have tetrahedral geometry except Pb(II) complex which has irregular tetrahedral geometry. 2010, INSInet Publication.